2000
DOI: 10.1007/s004410050010
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of P2X receptor subtypes in the rat female reproductive tract at late pro-oestrus/early oestrus

Abstract: Using immunohistochemistry techniques, we have examined the female reproductive organs of the rat in late pro-oestrus/early oestrus for the presence of purine nucleotide P2X1-7 receptors. In contrast to the male genital organs and the urinary tract, P2X1 receptors were present weakly, if at all, on smooth muscle membranes, except in blood vessels, whereas P2X2 immunoreactivity in smooth muscle was present in ovary and uterus as well as in blood vessels. Neither P2X1 nor P2X2 receptors were present in fallopian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
13
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(16 citation statements)
references
References 31 publications
3
13
0
Order By: Relevance
“…Very weak P2X 1 receptor immunoreactivity of the nonpregnant rat uterus has been described (23), and P2X 1 receptors have been identified in the uterine epithelial cells in nonpregnant rats and during early pregnancy (38,39). Adenosine 5 0 -triphosphate causes direct contraction of rodent myometrial smooth muscle cells in the nonpregnant (40)(41)(42)(43) and pregnant myometrium (44,45), probably acting via P2X 1 receptors.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Very weak P2X 1 receptor immunoreactivity of the nonpregnant rat uterus has been described (23), and P2X 1 receptors have been identified in the uterine epithelial cells in nonpregnant rats and during early pregnancy (38,39). Adenosine 5 0 -triphosphate causes direct contraction of rodent myometrial smooth muscle cells in the nonpregnant (40)(41)(42)(43) and pregnant myometrium (44,45), probably acting via P2X 1 receptors.…”
Section: Discussionmentioning
confidence: 97%
“…Preabsorption of the P2X 1 receptor antibody with an excess of the synthetic peptide eliminated immunoreactivity (23).…”
Section: Immunolabeling With P2x 1 Receptor and Cx43 Antibodiesmentioning
confidence: 99%
“…Immunoblotting studies have shown that anti-P2X 1-7 antibodies specifically recognise the recombinant receptors expressed in CHO-K1 cells (Oglesby et al 1999). Preabsorption of the antibodies with excess of the appropriate synthetic peptide used for generation of the antibodies eliminated immunoreactivity (see Xiang et al 1998aXiang et al , 1998bGröschel-Stewart et al 1999a;Bardini et al 2000).…”
Section: Ductus Epididymidismentioning
confidence: 97%
“…Data in the rat suggested that the P2X 5 and P2X 7 receptors play a role in the physiological turnover of continuously regenerating cells (Gröschel-Stewart et al, 1999;Bardini et al, 2000). In females, the P2X 4 receptor is involved in the regulation of tight junctional resistance and transepithelial transport across the vaginal epithelium, and possibly in the acidification of the luminal fluid, similar to effects observed in the endometrium and cervix (discussed above).…”
Section: Vagina and Vulvamentioning
confidence: 69%
“…Non-keratinizing squamous stratified epithelial cells of the vagina, and keratinizing squamous stratified epithelial cells of the vulva express P2X 4 (Gorodeski, 2002a), P2X 5 (Gröschel-Stewart et al, 1999Bardini et al, 2000), and P2X 7 receptors (Li et al, 2006a(Li et al, , 2007. Data in the rat suggested that the P2X 5 and P2X 7 receptors play a role in the physiological turnover of continuously regenerating cells (Gröschel-Stewart et al, 1999;Bardini et al, 2000).…”
Section: Vagina and Vulvamentioning
confidence: 94%